Association between genetic variants of the leukotriene biosynthesis pathway and the risk of stroke： a case-control study in the Chinese Han population - SUN, Hao; ZHANG, Jing; WANG, Jun; SUN, Tao; XIAO, Hang; ZHANG, Jin-song (Chinese medical journal, 2013)
Background Leukotrienes are arachidonic acid derivatives long known for their inflammatory properties. Leukotriene- based inflammation has been demonstrated to play a crucial role in atherosclerosis, a major risk factor for several human diseases. Recently, human genetic studies from us and others suggest that single nucleotide polymorphisms （SNPs） in leukotriene pathway genes influence the risk of atherosclerotic diseases such as stroke. This study aimed to assess the role of additional leukotriene pathway genes as a stroke risk factor within the Chinese Hart population. Methods We sequenced the promoter, exonic, and intronic regions of leukotriene A4 hydrolase （LTA4H） and arachidonate 5-1ipoxygenase （ALOX5）, and then genotyped five SNPs in LTA#H and four SNPs in ALOX5 among 691 cases with stroke and 732 controls from the Chinese population. Results We detected a significant association between an intronic SNP in LTA4H （rs6538697） and stroke in our subjects （adjusted odds ratio, recessive model, 1.75; P=0.022）; and the SNP rs2029253 in ALOX5 was associated with a decreased risk of stroke （adjusted odds ratio, 0.76; 95% confidence interval, 0.59-0.97）. Conclusion Genetic variants in LTA4H and ALOX5 may modulate the risk of stroke in the Chinese Han population.